Темний туризм як спосіб збереження історичної пам'яті - Скляренко, Анастасія Ігорівна; Sklyarenko, A. (Харків : Харківський національний університет імені В. Н. Каразіна, 2025)
Роботу присвячено дослідженню темного туризму як способу збереження історичної пам'яті. Досліджено сутність і основні підходи до визначення поняття «темний туризм». Детально розглянуто класифікацію його форм і проявів залежно від мотивації туристів, типів об’єктів та контексту подій. Вивчено закордонний досвід розвитку темного туризму. Проведено оцінку ресурсного потенціалу розвитку темного туризму в Україні, з урахуванням наявних об’єктів пам’яті, інфраструктурних можливостей і суспільного запиту. Проаналізовано сучасний стан темного туризму в Україні, окреслено ключові проблеми та бар’єри для його активізації. На основі проведеного аналізу визначено перспективні напрями розвитку темного туризму в контексті національної політики пам’яті, туристичної стратегії та освітньо-культурної діяльності.

This paper explores dark tourism as a mechanism for preserving historical memory and shaping collective identity. The research delves into the conceptual foundations of dark tourism, examining its definitions and the principal theoretical approaches to the phenomenon. A detailed classification of dark tourism forms is presented, structured around visitor motivations, types of sites, and historical contexts. The paper analyzes international experiences in the development of dark tourism, with particular reference to case studies from the United Kingdom, Germany, Poland, and Japan. Special attention is given to assessing the resource potential for dark tourism in Ukraine, taking into account memorial sites, infrastructure capabilities, and societal demand. The current state of dark tourism in Ukraine is examined, and key challenges and barriers to its expansion are identified. Based on the conducted analysis, the paper outlines strategic directions for the further development of dark tourism in alignment with national memory policy, tourism strategy, and cultural-educational initiatives.
Dark tourism as a means of preserving historical memory
Керівник: Сідоров Михайло Вадимович, кандидат економічних наук, доцент кафедри світової політики, дипломатії та туристичного бізнесу
Keywords: SOCIAL SCIENCES; темний туризм; туристичний потенціал; туризм; туристичні ресурси; dark tourism; tourism potential; tourism development; tourism; tourism resources